2015
DOI: 10.1073/pnas.1500247112
|View full text |Cite
|
Sign up to set email alerts
|

Self-affirmation alters the brain’s response to health messages and subsequent behavior change

Abstract: Health communications can be an effective way to increase positive health behaviors and decrease negative health behaviors; however, those at highest risk are often most defensive and least open to such messages. For example, increasing physical activity among sedentary individuals affects a wide range of important mental and physical health outcomes, but has proven a challenging task. Affirming core values (i.e., self-affirmation) before message exposure is a psychological technique that can increase the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
149
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(162 citation statements)
references
References 60 publications
11
149
1
1
Order By: Relevance
“…These successes depend on a fundamental understanding of the network interactions and the energy landscape defining how the brain moves between different states 101 , which predict not only common brain states, but also the probability of transitioning between them. In addition to methodological approaches to understanding these landscapes, open areas of inquiry include whether one can predict cognitive function from structural or functional network architecture 102 , predict disease onset or progression from early or pre-clinical data 103 , predict behavioral responses to health messaging 104 , or predict optimal strategies for early intervention.…”
Section: Current Frontiersmentioning
confidence: 99%
“…These successes depend on a fundamental understanding of the network interactions and the energy landscape defining how the brain moves between different states 101 , which predict not only common brain states, but also the probability of transitioning between them. In addition to methodological approaches to understanding these landscapes, open areas of inquiry include whether one can predict cognitive function from structural or functional network architecture 102 , predict disease onset or progression from early or pre-clinical data 103 , predict behavioral responses to health messaging 104 , or predict optimal strategies for early intervention.…”
Section: Current Frontiersmentioning
confidence: 99%
“…This study was a part of a larger investigation on neural predictors of health behavior change (reported in Cascio et al, 2016; Falk et al, 2015). Although health related outcomes are included in those previous reports, no reports using this data have focused on individual differences in mindfulness and subsequent motivation changes.…”
mentioning
confidence: 99%
“…Another alternative interpretation is that self-affirmation made people blind to the proposer’s feelings. Recent fMRI studies, however, have found that self-affirmation produces heightened activity in the ventromedial prefrontal cortex (vmPFC; Falk et al, 2015; Cascio et al, 2016), which is a brain area crucial for empathy (Botvinick et al, 2005). These findings suggest that affirmed participants might know better about how the proposers felt than unaffirmed participants.…”
Section: Discussionmentioning
confidence: 99%
“…A first ERP study showed that self-affirmation enlarges the error-related negativity (ERN) component, the amplitude of which further predicts performance errors, suggesting that self-affirmation increases the openness to mistakes via enhanced error-monitoring (Legault et al, 2012). A recent fMRI study indicated that self-affirmation increases the neural activity of vmPFC in response to health risk information, which in turn predicts declines in sedentary behavior (Falk et al, 2015). These findings suggest that self-affirmation reduces defensiveness by viewing otherwise threatening information as self-relevant.…”
Section: Discussionmentioning
confidence: 99%